Bringing the Law to the Library: The Importance of Librarian Mediation in Access to Justice Services. Issue 1 (2nd January 2018) - Patrice Jones, Yolanda
Abstract: Library access to justice programs and services help people who need legal information and who cannot afford an attorney. Librarian mediation is a critical component in the provision of access to justice services. However, the value of library mediation, or assistance with using library resources, is often unrecognized, particularly where members of the public are trying to access electronic legal information sources, online legal forms, and other law technologies. This article will explore the role of librarians in providing access to justice services from the perspective of the work of Richard Susskind, which emphasizes technological approaches to providing legal services. While there is a place for technology in access to justice services, there is also a valuable role that librarians play in contributing to access to justice.